A political ecology of women, water and global environmental change
1 online resource (xxvi, 262 pages)
Keywords: "This edited volume explores how a feminist political ecology framework can bring new and exciting insights to the study of livelihoods dependent on vulnerable rivers, watersheds, wetlands and coastal environments. Bringing together political ecologists and feminist scholars from multiple disciplines, the book develops solution-oriented advances to theory, policy and planning to tackle the complexity of these global environmental changes"--